Russian Federation : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper focuses on the potential to improve government efficiency and reduce opportunities for corruption in Russia by further improving fiscal transparency. The analysis presented here is in the context of the 2018 Framework for Enhanced IMF Engagement in Governance, which supports more systematic, candid, and even-handed engagement with member countries on this issue. The cross-country evidence presented confirms that fiscal transparency is broadly and robustly correlated with better outcomes. Improved outcomes include lower financing costs, better efficiency of public investment and revenue collection, and improved corruption perceptions. The IMF's fiscal transparency evaluations provide an alternative to the Open Budget Survey. In order to investigate the possibility of omitted variables, data presents result from panel regressions on the impact of fiscal transparency on corruption perceptions. Although regressions analysis can mitigate the risk of omitted variables, it leaves the issue of causality unresolved. Fully disentangling all the causal links among corruption, institutions, and economic development may not be feasible.